# Compute $\sum_{j=1}^k\cos^n(j\pi/k)\sin(nj\pi/k)$ [closed]

Compute the series

$\sum_{j=1}^k\cos^n(j\pi/k)\sin(nj\pi/k)$

Hint: the answer is in fact 0

## closed as off-topic by choco_addicted, user91500, M. Vinay, colormegone, WatsonApr 17 '16 at 8:42

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – choco_addicted, user91500, M. Vinay, colormegone, Watson
If this question can be reworded to fit the rules in the help center, please edit the question.

## 2 Answers

Recall that $\cos(x)=(e^{ix}+e^{-ix})/2$ and $\sin(x)=(e^{ix}-e^{-ix})/2i$, so your sum can be rewritten as

$$\sum_{j=1}^k\biggl[\frac{e^{j\pi i/k}+e^{-j\pi i/k}}2\biggr]^n\,\biggl[\frac{e^{nj\pi i/k}-e^{-nj\pi i/k}}{2i}\biggr]\,.$$

Applying binomial theorem on the first factor (of each summand) your sum becomes

\begin{align*} &\,\frac1{2^{n+1}i}\sum_{j=1}^k\sum_{r=0}^n\binom nr\bigl(e^{j\pi i/k}\bigr)^r\bigl(e^{-j\pi i/k}\bigr)^{n-r}\,\bigl[e^{nj\pi i/k}-e^{-nj\pi i/k}\bigr]\\[2mm] &\,\frac1{2^{n+1}i}\sum_{r=0}^n\binom nr\sum_{j=1}^k\bigl[e^{2rj\pi i/k}-e^{2j(r-n)\pi i/k}\,\bigr]\,. \end{align*}

Now $\sum_{j=1}^ke^{2rj\pi i/k}$ is the sum of a geometric progression, with sum equals to

$$e^{2r\pi i/k}\frac{e^{2rk\pi i/k}-1}{e^{2r\pi i/k}-1}=0\,,$$

because $e^{2r\pi i}=1$; similarly,

$$\sum_{j=1}^ke^{2j(r-n)\pi i/k}=e^{2(r-n)\pi i/k}\frac{e^{2(r-n)k\pi i/k}-1}{e^{2(r-n)\pi i/k}-1}=0\,,$$

and so all the inner summands above are equal to $0$.

• You lost a factor of $i$ in the denominator of the $\sin$ expansion. Of course it doesn't matter here since the result is $0$. Nice work. – Daniel Fischer Aug 25 '13 at 21:45
• @DanielFischer Thanks, correcting now. – Matemáticos Chibchas Aug 25 '13 at 21:50

Hint: by symmetry $\sum (\zeta+\zeta^{-1})^n\zeta^n=\sum (\zeta+\zeta^{-1})^n\zeta^{-n}$ as $\zeta$ is summed over the $k$th roots of $1$.